IN THE SPIRIT OF TRADITION, RELIGION AND MORAL EDUCATION: BOOK PRODUCTION IN DALMATIA OF THE FIRST HALF OF THE 19TH CENTURY - Lakuš, Jelena (Knygotyra, 2016)
The aim of this article is to investigate the character of book production in Dalmatia from 1815 when Dalmatia became an integral part of the Austrian Empire until the middle of the 19th century, the period dominated by the repressive politics of Chancellor Metternich (1809–1848) and his severe system of censorship. At the time, the publishing business still overlapped with the printing activity and it was limited to only five publishing houses situated in Zadar, Split and Dubrovnik. The article shows the results of the extensive research made according to two criteria: the intensity and (dis)continuity of book production as well as its subject and genre variety and/or uniformity. The analysis is based on a database resulting from archival research as well as from consulting many bibliographical sources and library catalogues. It shows that compared with the Western European countries of the age, whose annual production was expressed in thousands, book publishing in Dalmatia was quite restricted not only in numbers but also in the variety of subjects and genres. Metternich’s rigorous censorship, which constrained and regulated not only book production but also the entire system of dissemination and consumption of the printed word, as well as a religious revival that the Catholic Church in Dalmatia experienced at the time, were undoubtedly the most important causes for such a traditional and conservative character. The religious authorities claimed that moral education and spiritual knowledge was still the main purpose assigned to the printed word, considering it to be their sacred duty to safeguard the purity of faith and take care of the moral of their faithful, while the state authorities wished to direct beliefs and attitudes of their citizens, keeping them within an acceptable moral and political framework that led towards loyalty and obedience.
Keywords: Dalmatia; book production; publishing; 19th century; Austrian Empire